2020
DOI: 10.1530/eje-19-1051
|View full text |Cite
|
Sign up to set email alerts
|

MECHANISMS IN ENDOCRINOLOGY: Autoimmune hypopituitarism: novel mechanistic insights

Abstract: Hypopituitarism is caused by various insults to the pituitary, such as hypothalamic and pituitary tumors, inflammation, autoimmunity, vascular injury, genetic abnormalities, irradiation, and trauma. Recently, it has been found that autoimmunity to the pituitary involves many pathological conditions associated with specific or non-specific hormone deficiencies in the gland. This review discusses the recent findings on the underlying mechanism of autoimmune hypopituitarism particularly of lymphocytic hypophysiti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
37
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(39 citation statements)
references
References 61 publications
0
37
0
2
Order By: Relevance
“…SH is caused by a variety of inflammatory, infectious, vascular, and neoplastic conditions or as an adverse effect of various medications. Autoimmune hypophysitis results from autoimmunity-mediated destruction of the pituitary gland and is the commonest form of hypophysitis, including most cases of the PH category as well as the systemic autoimmune diseases of the SH forms [7].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…SH is caused by a variety of inflammatory, infectious, vascular, and neoplastic conditions or as an adverse effect of various medications. Autoimmune hypophysitis results from autoimmunity-mediated destruction of the pituitary gland and is the commonest form of hypophysitis, including most cases of the PH category as well as the systemic autoimmune diseases of the SH forms [7].…”
Section: Resultsmentioning
confidence: 99%
“…Hypophysitis is relatively rare, accounting for approximately 0.24–0.93% of all pituitary diseases [4, 8] – with its incidence constantly increasing with the widespread use of ICIs – and 0.4% of pituitary surgical cases [9]. PH is the commonest form of autoimmune hypophysitis [7]. PH has an incidence of 1/9 million/year and is classified according to etiology, anatomical location, and histopathology [4, 9].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…De Bellis et al demonstrated higher pituitary and hypothalamic antibody titers, respectively, in 14.8 and 18.5% of patients with isolated corticotrope deficiency [ 19 ]. Among corticotrope cell antibodies, Tpit antibodies are involved in the development of lymphocytic hypophysitis [ 20 ]. Tpit is an essential transcription factor for the development of corticotrope cells.…”
Section: Discussionmentioning
confidence: 99%
“…[17]. Наибольший интерес представляет аутоиммунная форма заболевания, к которой относятся лимфоцитарный, IgG4-ассоциирован ный [18].…”
Section: эндокринологияunclassified